Initiating the Implementation of Merging Crimes in Corruption Self-help Housing Stimulant Assistance - Cecep Ibnu Ahmadi; Dian Ekawati Ismail; Erman Rahim (Hang Tuah Law Journal, 2023)
Corruption in practice is not only a self-imposed crime but opens up space for other crimes both before and after the occurrence of corruption crimes. There are other criminal acts such as in the case of Self-Help Housing Stimulant Assistance in Pohuwato Gorontalo. However, in the process of law enforcement, only articles in the Corruption Law are used. Therefore, the focus of the problem in this paper is to examine the obstacles in investigating corruption in the Self-Help Housing Stimulant Assistance and how to apply the merger of criminal acts in corruption is implemented. The type of research used is normative research supported by empirical data. The results of this study indicate that the obstacles that affect the investigation of corruption in Self-Help Housing Stimulant Assistance consist of the minimum allocated budget, limited human resources, and facilities and infrastructure that are not following the cases handled. Meanwhile, the application of Article 263 of the Criminal Code in this case,  should have been carried out by the method of merging criminal acts, namely concursus realis, because the perpetrators carried out the initial act of forging signatures regulated in Article 263 of the Criminal Code and then resulted in the birth of corruption crimes charged with Article 2 of the Corruption Law.